Πρόβλεψη καθυστέρησης πτήσεων: μελέτη περίπτωσης στο Διεθνές Αεροδρόμιο Αθηνών Ελ. Βενιζέλος - Αθανασούλης, Αλέξανδρος (2019)
In this diploma thesis, we used data originated from Eleutherios Venizelos airport to analyze and predict flight departure delays. The goal of this thesis is first, to identify the factors which are most likely to cause flight delays and secondly to predict whether an individual flight will be delayed. Finally, if there is a delay, we would like to estimate its magnitude. We first describe important data features, along with preliminary pre-processing and analysis. Within this step, we use linear regression to identify the major factors that affect delays. Then we use logistic regression to predict whether there will be a delay and to calculate the magnitude of delays, we use linear regression. We first describe important data features, along with preliminary pre-processing and analysis. As part of this step, we use linear regression to identify the major factors that affect delays. Then we use logistic regression to predict whether there will be a delay and to calculate the magnitude of delays, we use linear regression.